Inter-datacenter bulk transfers with netstitcher - Laoutaris, Nikolaos; Yang, Xiaoyuan; Sirivianos, Michael (My University, 2011)
Large datacenter operators with sites at multiple locations dimension their key resources according to the peak demand of the geographic area that each site covers. The demand of specific areas follows strong diurnal patterns with high peak to valley ratios that result in poor average utilization across a day. In this paper, we show how to rescue unutilized bandwidth across multiple datacenters and backbone networks and use it for non-real-time applications, such as backups, propagation of bulky updates, and migration of data. Achieving the above is non-trivial since leftover bandwidth appears at different times, for different durations, and at different places in the world. For this purpose, we have designed, implemented, and validated NetStitcher, a system that employs a network of storage nodes to stitch together unutilized bandwidth, whenever and wherever it exists. It gathers information about leftover resources, uses a store-and-forward algorithm to schedule data transfers, and adapts to resource fluctuations. We have compared NetStitcher with other bulk transfer mechanisms using both a testbed and a live deployment on a real CDN. Our testbed evaluation shows that NetStitcher outperforms all other mechanisms and can rescue up to five times additional datacenter bandwidth thus making it a valuable tool for datacenter providers. Our live CDN deployment demonstrates that our solution can perform large data transfers at a much lower cost than naive end-to-end or store-and-forward schemes